Co-immobilization of enzymes with the help of a dendronized polymer and mesoporous silica nanoparticles1. Issue 30 (14th August 2015) - Gustafsson, Hanna; Küchler, Andreas; Holmberg, Krister; Walde, Peter
<x xml:space="preserve">Abstract</x> Two enzymes were immobilized in close proximity to each other using enzyme-containing mesoporous nanoparticles and a dendronized polymer–enzyme hybrid structure.